Digitalisation, knowledge management and technology transfer impact on organisations' circularity capabilities - Tadas Radavičius; Manuela Tvaronavičienė (Insights into Regional Development)
Transition to circular economy (CE) requires that organisations change the way they do activities. Through digitalisation the information flow can be improved across all the value chain. The information that is particularly relevant for CE needs to be created in the first place and shared within the organisation and among them to implement CE strategies. Implementation of CE strategies requires that organisations has the ability to access technologies through technology transfer to achieve higher co-operation levels. Circular processes can be defined as those processes within organisations that positively contributes towards CE principles implementation, such as re-using or recycling products and materials. Within this article knowledge management (KM), digitalisation, and technology transfer (TT) are analysed through systematic literature review to understand the impact of these three concepts on organisations capabilities to develop circular processes. The knowledge management theory demonstrate the need for higher attention on how within organisations and between organisations CE related information could be managed to achieve CE strategies for organisations and their networks, such as supply chain. Technology transfer ensures that there are pathways to transfer relevant technologies that can improve or enable CE processes to multiple organisations through open source or conditional transfers. A concept based on a literature review is proposed on how digitalisation facilitates knowledge management within & among organisations, improves decision making of circular processes, and enables CE strategies implementation.